Association between Concentration of Air Pollutants and Prevalence of Inflammatory Sinonasal Diseases: A Nationwide Cross-sectional Study. Issue 5 (September 2022) - Han, Munsoo; Choi, Soo Jeong; Jeong, Yujin; Lee, Kijeong; Lee, Tae Hoon; Lee, Sang Hag; Kim, Tae Hoon
Background: Air pollution is a serious health concern and affects inflammatory sinonasal diseases such as allergic rhinitis (AR) and chronic rhinosinusitis (CRS). Clarifying the relationship between air pollutants and upper respiratory diseases could help the patients. Objective: To evaluate the association between the concentration of air pollutants and the prevalence of AR and CRS among South Koreans. Methods: In this cross-sectional study, nationwide data were reviewed for participants of the Korean National Health and Nutrition Examination Survey (KNHANES) 2008 to 2012. Participants were surveyed with health questionnaires, examined with endoscopies by otolaryngologists, and tested with serum immunoglobulin E levels. The concentrations of sulfur dioxide (SO2 ), nitrogen dioxide (NO2 ), ozone (O3 ), and particulate matter with aerodynamic diameters ≤10 µm (PM10 ) were measured in 16 areas of South Korea. Air pollutant concentrations of geographic districts were matched to each participant's residence. Logistic regression analysis was performed. Results: Among 27 863 eligible adults, 3359 and 1606 participants had AR or CRS, respectively. In multivariable logistic regression analysis for AR, PM10 showed statistically significant results (odds ratio [OR] = 1.145, 95% confidence interval [CI] = 1.042–1.258). No air pollutants showed statistically significant differences in the prevalence of CRS. In AR, PM10 (OR = 1.458, 95% CI = 1.201–1.770) was associated with endoscopic findings of watery rhinorrhea, whereas SO2 (OR = 1.202, 95% CI = 1.100–1.313) was associated with pale mucosa. Conclusion: The prevalence of AR was significantly associated with PM10 concentration. In patients with AR, endoscopic findings of watery rhinorrhea were associated with PM10 . However, CRS was not associated with the air pollutant concentrations. Lower concentration of PM10 might help managing the clinical symptoms in patients of AR.